Detail of Sod Roof at Straumen Farm, Northern Norway - Campbell, Sandy (2024)
Most of the buildings at the Straumen Farm in Tromsø Municipality, Norway have sod rooves. These rooves have a layer of birch bark which is covered with sod. In this image you can see the birch bark at the bottom of the sod. The sod is alive with moss, lichen, grasses and other plants growing on it. Rooves built in this way can last 50 - 70 years.